Subarachnoid Hemorrhage and Prostatic Involvement in Granulomatosis with Polyangiitis – An Atypical Presentation - Raymond Bak Hei Chu; Priscilla Ching Han Wong; Joey Ka Ming Wai; Florence Hiu Yi Yap (Journal of Clinical Rheumatology and Immunology, 2019)
Granulomatosis with Polyangiitis (GPA) is a form of Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis. We report a case of a 56-year-old man with GPA who first presented with acute urinary retention, and then developed pulmonarycavitating lesions and subarachnoid hemorrhage (SAH). The SAH was due to a ruptured right vertebral artery aneurysm, whichwas subsequently embolized. The patient initially had a good response to immunosuppressive therapy but later succumbed due to fulminant sepsis. SAH is a rare complication of GPA and usually not associated with a detectable aneurysm. Our patient is thesecond case in the literature where an aneurysm had been detected on angiography and the first case where examination of the culprit aneurysm revealed features of vasculitis.